2016
DOI: 10.1371/journal.pone.0148198
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Inducing Melanoma Cell Apoptosis Activity of Mannosylerythritol Lipids-A Produced from Pseudozyma aphidis

Abstract: Mannosylerythritol lipids (MELs) are natural glycolipid biosurfactants which have potential applications in the fields of food, cosmetic and medicine. In this study, MELs were produced from vegetable oil by Pseudozyma aphidis. Their structural data through LC/MS, GC/MS and NMR analysis revealed that MEL-A with two acetyls was the major compound and the identified homologs of MEL-A contained a length of C8 to C14 fatty acid chains. This glycolipid exhibited a surface tension of 27.69 mN/m at a critical micelle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

5
4

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 38 publications
0
21
0
Order By: Relevance
“…Secondly, the ability to inhibit the growth of cancer cell by MEL-A itself is also an important cause. It has been reported that MEL-A could inhibit growth and promotes cell differentiation in melanoma B16 cells and leukemia HL60 and K562 cells [28]. However, the survival rate of HepG2 cells increased to some extent at low concentration of SCM, due to the inhibitory activity of MEL-A is weak at a low concentration in the liposome system, and its surface property facilitates the uptake of nutrients by cancer cells, the specific reason of which still remains to be studied.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, the ability to inhibit the growth of cancer cell by MEL-A itself is also an important cause. It has been reported that MEL-A could inhibit growth and promotes cell differentiation in melanoma B16 cells and leukemia HL60 and K562 cells [28]. However, the survival rate of HepG2 cells increased to some extent at low concentration of SCM, due to the inhibitory activity of MEL-A is weak at a low concentration in the liposome system, and its surface property facilitates the uptake of nutrients by cancer cells, the specific reason of which still remains to be studied.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to other biosurfactants, for example, rhamnolipids and sophorolipids, MELs own many excellent physicochemical properties such as good emulsifying properties, biodegradability, and lower critical micelle concentration (CMC), but also many special physiologic activities, such as inhibiting the growth of microorganisms (Kitamoto et al, ), inducing cell mutation (Isoda & Nakahara, ; Wakamatsu et al, ), differentiate human myeloid leukemia cell lines and melanoma cells (Fan, Li, Niu, & Chen, ; Zhao et al, ), improving the efficiency of gene transfection (Kitamoto, ), and a strong coordination ability with glycoproteins (Fan, Xie, Wang, Huang, & Zhou, ; Im, Nakane, Yanagishita, Ikegami, & Kitamoto, ; Im et al, ); thus, MELs could be used in lots of industries (Morita, Fukuoka, Imura, & Kitamoto, ; Noh, Suh, & Park, ; Safdel, Anbaz, Daryasafar, & Jamialahmadi, ), for example, environmental protection, food, cosmetic, and pharmaceutical.…”
Section: Introductionmentioning
confidence: 99%
“…MEL has been exploited in many fields such as potent antimicrobial activity and interfacial properties (Morita et al 2006). As well, MEL shows numerous bioactivities, such as, induce cells of apoptosis and differentiation of mouse melanoma, rat pheochromocytoma and extensively applied in food, pharmaceutical, cosmetic and environmental protection (Zhao et al 1999; Wakamatsu et al 2001; Fan et al 2016).
Fig.
…”
Section: Introductionmentioning
confidence: 99%